A review on solar pavement and photovoltaic/thermal (PV/T) system. (April 2021) - Zhou, Bochao; Pei, Jianzhong; Nasir, Diana Mohd; Zhang, Jiupeng
Highlights: Research on solar pavement and PV/T system was comprehensively reviewed. The concept of pavement integrated photovoltaic/thermal system (PIPVT) was proposed. The initial design of the PIPVT was proposed. The design of PIPVT can improve solar comprehensive utilization efficiency. The heat pipe of PIPVT can increase the life of PV cells by heat dissipation. Abstract: In recent years, highway construction field has made huge efforts to develop energy harvesting solutions, such as solar pavement, which mainly on photovoltaic (PV) pavement and thermal energy harvesting pavement. Due to low energy utilisation efficiency and short operating life of PV cells without heat dissipation, the concept of pavement integrated photovoltaic/thermal system (PIPVT) is proposed, which organically combines the above two main solar pavements. Since there is no available research on PIPVT technology for roads, a comprehensive review on building integrated photovoltaic/thermal (BIPVT) system, the PV pavement, and thermal energy harvesting pavement were made to explore the technical feasibility of PIPVT. The initial design of PIPVT has been proposed according to the findings of our previous works, which can improve solar comprehensive utilisation efficiency, as well as the life of PV cells in theory. This review can provide new ideas for future research on energy harvesting pavement.